2018
DOI: 10.1158/0008-5472.can-17-1467
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy Induced by Microtubule-Targeted Chemotherapies: Insights into Acute Injury and Long-term Recovery

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a major cause of disability in cancer survivors. CIPN investigations in preclinical model systems have focused on either behaviors or acute changes in nerve conduction velocity (NCV) and amplitude, but greater understanding of the underlying nature of axonal injury and its long-term processes is needed as cancer patients live longer. In this study, we used multiple independent endpoints to systematically characterize CIPN recovery in mice exposed to the anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…This is an analogue of halichondrin B (toxin from the sponge Halichondria okadai ), is a newer chemotherapeutic agent that also binds to tubulin and affects microtubule dynamics . Likewise, the effect of eribulin is primarily microtubule depolymerization, which also has been shown to disrupt axonal transport leading to neuropathy in animal models …”
Section: Pathogenetic Considerationsmentioning
confidence: 99%
“…This is an analogue of halichondrin B (toxin from the sponge Halichondria okadai ), is a newer chemotherapeutic agent that also binds to tubulin and affects microtubule dynamics . Likewise, the effect of eribulin is primarily microtubule depolymerization, which also has been shown to disrupt axonal transport leading to neuropathy in animal models …”
Section: Pathogenetic Considerationsmentioning
confidence: 99%
“…It is a commonly used chemotherapeutic drug for treatment of solid cancers such as breast, ovarian and lung cancers by virtue of its ability to inhibit cell division. Paclitaxel is more likely than other chemotherapeutics to cause chronic sensory neuropathy in patients and animal models (Gornstein and Schwarz, 2014;Hershman et al, 2011;Majithia et al, 2016;Shah et al, 2018;Wozniak et al, 2018;Xiao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both schedules are associated with cumulative toxicity, including neurotoxicity, which is the main cause of cancer disability. 77 As a result, treatment holidays or treatment-free periods have been introduced; however, preclinical data suggest that longer taxane-free intervals might be associated with treatment resistance. 78,79 Ovarian cancer xenograft models have shown that continuous administration of taxanes is associated with less treatment resistance, including drug resistance-related genes and drug efflux transporter expression, as well as reduced tumor growth and proliferation.…”
Section: Platinum-sensitive Recurrencementioning
confidence: 99%
“…Given the risk of cumulative toxicity of cisplatin and paclitaxel chemotherapy, including renal impairment and neuropathy, clinicians often must stop the chemotherapy treatment or stop one of the drugs soon after six cycles have been delivered. 77,94,95 The role of bevacizumab as a single-agent maintenance treatment has not yet been explored as part of the GOG-240 clinical trial, and this has led to concerns for regulatory agencies when only single-agent bevacizumab is administered as maintenance treatment.…”
Section: Cervical Cancermentioning
confidence: 99%